Operations research an introducton - Taha, Hamdy A. (Pearson, 2023)
"This edition maintains the time-proven pedagogical features of the first ten editions: All algorithmic details are explained by carefully chosen numerical examples that contribute to one's intuition regarding the general problem. Theorems and proofs are used only when needed to maintain continuity. The focal points that unify algorithms within an optimization area (e.g., LP) are stressed to provide insight about the functionality of each algorithm. For example, the plethora of available simplex method algorithms may give the impression that they are fundamentally different when, in fact, they all are based on the one idea of seeking extreme- or corner-point solutions"--